Short term safety of oncoplastic breast conserving surgery for larger tumors. Issue 4 (April 2017) - Wijgman, D.J.; ten Wolde, B.; van Groesen, N.R.A.; Keemers-Gels, M.E.; van den Wildenberg, F.J.H.; Strobbe, L.J.A.
Abstract: Background: Oncoplastic surgery (OPS) replaces lumpectomy as standard technique in breast conserving surgery (BCS). OPS has shown to give good cosmetic results, but is it as safe as standard lumpectomy? We conducted a retrospective cohort study to determine postoperative complications, resection margins and re-excision rates for OPS compared to standard lumpectomy. Methods: Based on data from the 'Netherlands Cancer Registry' and medical records we scored patient, treatment and follow-up related variables. All consecutive patients, with an initially breast conserving operation for primary breast cancer, performed between January 2010 and December 2014 in a dedicated breast center were eligible. Breast surgeons performed the operations. Invasive and in situ tumors were included. Postoperative complications within 30 days after surgery and the need for additional treatment were classified using the Clavien Dindo classification. Involved margin rates and subsequent re-excision were compared. Results: We included 828 women with 842 breast cancers, who had a standard lumpectomy (62.7%) or oncoplastic resection (37.3%). OPS was performed more often for larger tumors (17.5 mm vs 13.6 mm, p = 0.002) and for tumors in the caudal half of the breast (33.1% vs 16.9%, p < 0.001). There was no significant difference in postoperative complications. Positive surgical margins were similar (OPS 22.6%, lumpectomy 18.2%, p = 0.119), as were re-excision rates (p = 0.337). Conclusion: Oncoplastic breast surgery can be safely applied in larger tumors, resulting in comparable postoperative complications, resection margins and re-excision rates compared to standard lumpectomy.